KLASIFIKASI JURUSAN MENGGUNAKAN METODE NAÏVE BAYES PADA SEKOLAH MENENGAH ATAS NEGERI (SMAN) 1 FATULEU TENGAH - Arrdy Hailitik; Bertha S Djahi; Yelly Y Nabuasa (Universitas Nusa Cendana, 2017)
Naïve bayes is the classification method which utilizes the both probabilities and statistics to predict the future opportunity by using the last experiance. The system of major in the senior high school is the means of students directing to be more based on their interest and academic competence. The major in East SMAN 1 Fatuleu consists of the Science and Social majors. This research is using the Method of Naïve bayesto classify the student major. The data of student that is used here is the grade XI for second semester in the years of 2011 to 2015 with the 470 for the total data. For the testing proces is used 420 data (89%) as trains data and 50 data (11%) as tests data. The result of this research shows the amount of 99.31% accuracy in the process of major classification.